Corrigendum: Revealing the mechanism of Huazhi Rougan granule in the treatment of nonalcoholic fatty liver through intestinal flora based on 16S rRNA, metagenomic sequencing and network pharmacology - Liu, Yingying; Tan, Yingying; Huang, Jiaqi; Wu, Chao; Fan, Xiaotian; Stalin, Antony; Lu, Shan; Wang, Haojia; Zhang, Jingyuan; Zhang, Fanqin; Wu, Zhishan; Li, Bing; et al. (Frontiers in Pharmacology, 2023)
Graphical Abstract